RANKING OF TRIANGULAR FUZZY NUMBER METHOD TO SOLVE AN UNBALANCED ASSIGNMENT PROBLEM - SRI PRAKASH, K. SANGEETHA; H, HASEENA BEGUM; ANAND BABU, M. PAVITHRA (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In this paper, we proposed to solve the fuzzy salesman problem using Hungarian method. An unbalanced assignment problem is solved using Ranking of Triangular Fuzzy number. In this paper, first the proposed unbalanced assignment problem is formulated to a crisp assignment problem and solved by using Hungarian method and using Ranking of Triangular Fuzzy number. Numerical examples show that the fuzzy ranking method offers an effective tool for handling the unbalanced assignment problem.